The pathophysiological mechanisms of immunosenescence in coronary artery disease - Bie, Hengjie; Tao, Zhengxian (Frontiers in Cell and Developmental Biology, 2025)
Coronary artery disease (CAD) is the most common coronary heart disease, characterized by the accumulation of atherosclerotic plaques in the coronary arteries, which supply oxygen and nutrients to the heart. The National Health and Nutrition Examination Survey (NHANES) reported that between 2011 and 2014, the prevalence of coronary artery disease was higher in men (30.6%) than in women (21.7%) aged ≥80 years. In the ARIC (Atherosclerosis Risk in Communities) study, the incidence of myocardial infarction (MI) was higher in black individuals compared to white individuals among those aged 65–84 years. Immunosenescence plays a pivotal role in its onset and progression. Immunosenescence is a complex process involving organ remodeling and cellular regulation, leading to a decline in immune function and reduced responses to infection and vaccination in older adults. By driving dysfunction in multiple immune cell populations—including T cells, B cells, and macrophages—immunosenescence promotes chronic inflammation, vascular injury, and the advancement of atherosclerotic plaques. In recent years, intervention strategies targeting immunosenescence—such as restoration of hematopoietic stem cell function, reconstitution of T- and B-cell compartments, modulation of macrophage polarization and effector programs, and thymic regeneration—have made substantive progress. Future research should prioritize elucidating the mechanisms of immunosenescence, advancing the development of personalized therapeutic strategies, and rigorously validating their efficacy and safety in clinical trials; therapeutic modulation of immunosenescence holds promise for improving treatment outcomes and prognosis in patients with CAD.